Are long-haul truck drivers unusually alert? A comparison with long-haul airline pilots. (March 2020) - Sallinen, Mikael; Pylkkönen, Mia; Puttonen, Sampsa; Sihvola, Maria; Åkerstedt, Torbjörn
Highlights: Long-haul truck drivers rate lower sleepiness levels than long-haul airline pilots. Predicted sleepiness levels do not differ between these occupational groups. Long-haul truck drivers may be sleepier than they report. Long-haul truck drivers may underreact to sleepiness. Abstract: Background: Recent studies suggest heavy vehicle drivers self-estimate their sleepiness unexpectedly low during night duties. The present study compared sleepiness ratings of long-haul truck drivers with those of long-haul airline pilots during night and non-night duties. In addition, the correspondence between self-rated manifest and predicted latent sleepiness was examined in the two groups. Methods: Twenty-two drivers and 33 pilots participated. Their working hours, sleep, on-duty sleepiness, and use of sleepiness countermeasures were measured in naturalistic conditions. Predictions of latent sleepiness were based on the measurements of working hours and sleep using the Sleep/Wake Predictor modelling tool. Results: Drivers rated lower levels of sleepiness than pilots during both duty types, though predicted latent sleepiness levels were very similar among the two groups. Neither the results of sleep nor those of sleepiness countermeasures explained the difference in self-rated sleepiness. Discussion: The results raise the possibility that long-haul truck drivers are actually sleepier than they report, and thus are at an increased risk for not responding to sleepiness in a timely manner. A potential explanation for this behavior is lack of education and training on sleepiness among truck drivers as compared with airline pilots. Alternatively, long-haul truck drivers may be exceptionally tolerant to soporific working conditions. The first reported results do not, however, support this hypothesis.